Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper analyzes the competitive threats to the tourism sector in the Eastern Caribbean Currency Union (ECCU). The paper concludes that the ECCU countries have lost competitiveness globally and vis-a-vis newly emergent Caribbean tourist destinations as a result of both price and nonprice factors. The short-term measures implemented by the countries seem to have been insufficient to prevent further declines in 2002. The paper also describes strengthening fiscal discipline through fiscal benchmarks.